The Failure of Foreign Direct Investment to Explain Unemployment Rate and the Mediating Role of Economic Growth and Minimum Wage - Tegep, Jumhur; Suratman, Eddy; Indra, Sukma (International Journal of Economics and Financial Issues, 2019)
This research aims to discover and test macroeconomic variables which can mediate the relationship between Foreign Direct Investment (FDI) and unemployment rate in Indonesia. Employing integrated alternative model using macroeconomic variable as mediating factors, it uses path analysis to test a panel data from 36 Indonesian provinces within 17 years (422 observations). In order to calculate inter-variables’ direct effects, it employs bootstrapping method. This study successfully found that Gross Domestics Product (GDP) and provincial minimum wage can directly mediate FDI and unemployment rate. On the other hand, domestic investment and the number of workforces cannot mediate the relationship between FDI and unemployment rate. These results confirm that FDI cannot directly explain the change in unemployment rate without the mediation of economic growth and provincial minimum wage in Indonesian labor market. FDI’s inability to directly explain unemployment is because the existing investment is capital- and technology-intensive; hence, at the first stage, it influences output growth more. To conclude, government policy to attract FDI needs to be followed by other policies aiming to enhance the skill of local labors, so that they can be absorbed by FDI. Keywords: economic growth, investment, unemployment rate, mediating variable JEL Classifications: E24, F21, F43 DOI: https://doi.org/10.32479/ijefi.7524